2011
DOI: 10.1016/j.pbb.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

SA 4503 attenuates cocaine-induced hyperactivity and enhances methamphetamine substitution for a cocaine discriminative stimulus

Abstract: Cocaine exhibits preferential (∼15-fold) affinity for σ 1 over σ 2 sigma receptors, and previous research has shown an interaction of σ 1 receptor-selective ligands and cocaine's behavioral effects. The present study investigated the effect of the putative sigma receptor agonist SA 4503 (1-(3,4-dimethoxyphenethyl)-4-(3-phenylpropyl)piperazine dihydrochloride) on cocaine's locomotor stimulatory and discriminative stimulus properties. At doses without intrinsic activity, SA 4503 dose-dependently attenuated cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…One difference between studies is the cocaine dose employed, which was 10 mg/kg (33 mmol/kg) in the Akunne study and 20 mg/kg (66 mmol/kg) in the present study. Previous dose-response profiles show a relatively small difference, on the order of 20%, in the levels of locomotor hyperactivity induced by these doses of cocaine in either Swiss Webster (Menkel et al, 1991) or CD-1 mice (Rodvelt et al, 2011). Consequently, cocaine dosage is not likely to have had a major impact.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One difference between studies is the cocaine dose employed, which was 10 mg/kg (33 mmol/kg) in the Akunne study and 20 mg/kg (66 mmol/kg) in the present study. Previous dose-response profiles show a relatively small difference, on the order of 20%, in the levels of locomotor hyperactivity induced by these doses of cocaine in either Swiss Webster (Menkel et al, 1991) or CD-1 mice (Rodvelt et al, 2011). Consequently, cocaine dosage is not likely to have had a major impact.…”
Section: Discussionmentioning
confidence: 89%
“…Effects of PD144418 on basal locomotor activity and cocaine-induced locomotor stimulation in mice were evaluated by procedures similar to those used previously for evaluations of other s receptor ligands (Rodvelt et al, 2011;Sage et al, 2013). Experiments were performed in activity monitors (Model ENV-515; Med Associates Inc., Georgia, VT) consisting of a transparent box surrounded by banks of infrared sensors that were connected to a computer.…”
Section: Methodsmentioning
confidence: 99%
“…However, METH has previously been shown to substitute for cocaine in mice trained to discriminate cocaine from saline (eg, Rodvelt et al, 2011), and we have previously reported that cocaine produces full generalization in mice trained to discriminate S( þ )-MDMA or R( À )-MDMA from saline (Murnane et al, 2009). Similarly, Johanson et al (2006) reported that humans could be trained to discriminate among 20 mg d-amphetamine, 0.75 mg/kg mCPP and placebo, and that when tested with 1.0 and 1.5 mg/kg MDMA, half the participants reported MDMA to be amphetamine-like and half reported it to be mCPP-like.…”
Section: 4-methylenedioxypyrovalerone In Micementioning
confidence: 99%
“…Non-radioactive E -IA-DM-PE-PIPZE also partially attenuates (−)-cocaine induced locomotor hyperactivity, suggesting antagonist character [58]. At present, such behavioral studies are a principal way to assign the functional properties of σ 1 receptor ligands [38,64,179,180]. Dopamine transporter (DAT) inhibition is recognized as the main contributor to (−)-cocaine’s behavioral effects and abuse liability.…”
Section: Preclinical Imagingmentioning
confidence: 99%